2013
DOI: 10.1097/rhu.0b013e3182a21ba8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Polymyositis and Dermatomyositis in a Health Management Organization in Buenos Aires

Abstract: It is difficult to compare studies from different populations and using different ascertainment techniques. These first data from Latin America are in general agreement with many studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…As for the prevalence of alopecia areata, Addison's disease, antiphospholipid syndrome, celiac disease, Crohn's disease, myasthenia gravis, polymyositis, and immune thrombocytopenic purpura, all had the same prevalence level in the present study (1.6 per 100,000) but were lower than the prevalence studies respectively consulted (100/200, 0.45/11.7, 40/50, 1,000/2,000, 5.65, 14.2, 7.2, and 11.2 per 100,000) [65][66][67][68][69][70][71][72], suggesting that the small number of cases may be due to the fact that these pathologies are considered rare and the underdiagnosis related to problems with referral flow and counter-referral of users when accessing consultations [73,74].…”
Section: Distribution Of the Sociodemographic Profile Of The Samplesupporting
confidence: 43%
“…As for the prevalence of alopecia areata, Addison's disease, antiphospholipid syndrome, celiac disease, Crohn's disease, myasthenia gravis, polymyositis, and immune thrombocytopenic purpura, all had the same prevalence level in the present study (1.6 per 100,000) but were lower than the prevalence studies respectively consulted (100/200, 0.45/11.7, 40/50, 1,000/2,000, 5.65, 14.2, 7.2, and 11.2 per 100,000) [65][66][67][68][69][70][71][72], suggesting that the small number of cases may be due to the fact that these pathologies are considered rare and the underdiagnosis related to problems with referral flow and counter-referral of users when accessing consultations [73,74].…”
Section: Distribution Of the Sociodemographic Profile Of The Samplesupporting
confidence: 43%
“…Interestingly, it was noted that scleroderma patients in these areas were more likely to drink alcohol [38]. In southern Australia, a lower prevalence of DM was reported [33] compared to other countries as well as Olmsted County [9, 32, 34, 35]. This study found a possible association between DM and a higher socioeconomic status [33].…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of BD was significantly higher in Turkey [31] compared to Olmsted County [8], other European countries and Taiwan [2830]. The prevalence of DM in central Greece [35] was relatively high compared to the prevalences in the USA, Australia, and Argentina [9, 3234]. The prevalences of scleroderma in Detroit, Mich., USA [36], areas of Canada [37, 38], and South Australia [39] were higher than the prevalence reported in Olmsted County [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the numerous advances in recent years for the treatment of RA may have changed the OP epidemiology in these patients. Our objective was to compare the incidence of fragility fractures in rheumatoid arthritis patients diagnosed after the year 2000 with matched controls from a University hospital-based health management organization (HMO) [13,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%